Spotlight on romiplostim in the treatment of children with chronic immune thrombocytopenia: design, development, and potential place in therapy - Buchbinder D; Nugent D; Hsieh L (Dove Medical Press, 2017)
David Buchbinder, Diane Nugent, Loan Hsieh Division of Hematology, CHOC Children’s Hospital and UC Irvine Medical Center, CA, USA Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune disorder characterized by isolated thrombocytopenia. In approximately one-third of cases, the duration of thrombocytopenia will extend beyond 12 months consistent with a diagnosis of chronic ITP. Minor bleeding manifestations are common in chronic ITP while severe or life-threatening bleeding complications are uncommon. Moreover, spontaneous resolution occurs in the majority of children with chronic ITP necessitating treatment in only those children with ongoing bleeding manifestations or impairment in health-related quality of life (HRQOL). The characterization of thrombopoietin (TPO) and remarkable advancements in our understanding of the pathophysiology of ITP has led to the development of a new class of agents, the TPO-receptor agonists that have documented efficacy in the amelioration of thrombocytopenia and bleeding manifestations in chronic ITP. Romiplostim is a second-generation TPO-receptor agonist that has undergone limited evaluation in the treatment of chronic ITP in children. Evolving data suggest that romiplostim may be a safe and effective agent in the treatment of chronic ITP in children. Additional data are needed to confirm its ability to increase platelet counts, decrease bleeding manifestation, and improve the HRQOL of children and caregivers impacted by chronic ITP. Keywords: thrombocytopenia, chronic, thrombopoietin, childhood